Adapting to Climate Change in Europe and Central Asia : Lessons from Recent Experiences and Suggested Future Directions - World Bank (Washington, DC, 2013)
Like other regions, Eastern Europe and Central Asia is vulnerable to climate change and its potential socioeconomic impacts. While all countries are facing warmer temperatures, a changing hydrology, and more extreme events (for example, floods and droughts) and are concerned about the level of greenhouse gases in the atmosphere, they differ in their financial and institutional capacities to respond. Therefore, especially for the most vulnerable countries in the region (for example, those in Central Asia and southern Europe), adapting to climate risk adds a new dimension to the challenges of development, but also provides an opportunity to revisit priorities and accelerate reforms. The Europe and Central Asia (ECA) Region of the World Bank has been actively working on climate-related projects and has advanced a number of initiatives in response to climate change since the 1990s. Nevertheless, up until a few years ago the region's focus was mainly on emissions reduction (mitigation), rather than on helping countries respond to existing or expected impacts from climate change through adjustments in natural or human systems. But more recently, adding focus on climate adaptation had led ECA to initiate a program of analytical work and pilot investment projects to help develop the information and knowledge base necessary to help build staff skills as well as better respond to client needs.